Network+ guide to networks - Dean, Tamara (Networking series., 2013)
The completely updated NETWORK+ GUIDE TO NETWORKS, 6th Edition gives readers the technical skills and industry know-how required to begin an exciting career installing, configuring, and troubleshooting computer networks. The text also prepares readers for CompTIA's Network+ N10-005 certification exam with fundamentals in protocols, topologies, hardware, and network design. After exploring TCP/IP, Ethernet, wireless transmission, and security concepts, as well as an all-new chapter on virtual networks, readers can increase their knowledge with the practical "On-the Job" stories, Review Questions, Hands-On Projects, and Case Projects. NETWORK+ GUIDE TO NETWORKS, 6th Edition also includes reference appendices, a glossary, and full-color illustrations. The features of the text combined with its emphasis on real-world problem solving, provides readers with the tools they need to succeed in any computing environment.